Exploring EFL Students’ Psychological Well-Being in Boarding University Environment - Jessenianta, Aurel Keisha; Khoir, Azizatul; Metriyandani, Azka Amara; Rohmana, Wahyu Indah Mala (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research focuses on the psychological well-being of EFL students living in university dormitories. Entering university marks the transitional period for the young generations. Through this transition, students faced new challenges such as making independent decisions about their lives and their studies, and engaging with various new people in the academic environment of a non-synchronous learning environment. In this context, research into the wellbeing of EFL students during university intermission is necessary to understand the impact of university environments and specific programmes such as compulsory residence on the well-being of students, especially those studying English as a foreign language (EFL). this study utilized a quantitative descriptive approach, with questionnaires as the primary data collection tool. Through this approach, the researcher aims to objectively describe the perspectives and experiences of the participants. The quantitative data obtained from structured questionnaires were analyzed to provide a comprehensive overview of the theme of student well-being within the context of this research. The findings from this study provide valuable insights into the psychological well-being of EFL students in a boarding university environment, analyzed through Ryff''s six dimensions of psychological well-being: autonomy, environmental mastery, personal growth, self-acceptance, purpose in life, and positive relations. Overall, the results indicate that students exhibit a high level of autonomy, environmental mastery, and self-acceptance, with particularly strong scores in personal growth. However, areas such as environmental mastery (specifically campus resource utilization), social engagement, and self-expression highlight opportunities for further support and improvement.